Acupuncture for hormonal readiness and gut microbiota in obese polycystic ovary syndrome: an open-label, randomized controlled trial - Wu, Tianyu; Xu, Guixing; Hong, Xiaojuan; Fan, Huaying; Zeng, Jiuzhi; Liu, Yu; Hu, Jinqun; Liang, Fanrong; Yang, Jie; Chen, Jiao (Frontiers in Endocrinology, 2024)
Objective: To explore whether acupuncture combined with clomiphene can reduce the luteinizing hormone-to follicle-stimulating hormone ratio and impact the gut microbiota in patients with obese polycystic ovary syndrome.Methods: This open-label, randomized, parallel-group controlled trial included 86 women aged 20-40 years with obese polycystic ovary syndrome and 19 healthy controls. Participants were randomly assigned to either an acupuncture combined with clomiphene group or a clomiphene-only group, with a healthy control group for comparison. The treatment lasted three menstrual cycles, with acupuncture administered three times weekly and clomiphene given daily from day five of menstruation for five consecutive days per cycle. The primary outcome was the change in the luteinizing hormone-to-follicle-stimulating hormone (LH/FSH) ratio. Secondary outcomes included levels of other sex hormones, glucose and lipid metabolism parameters, self-rating anxiety and depression scale scores, and gut microbiota composition.Results: Intention-to-treat analysis showed that the adjusted mean luteinizing hormone-to folliclestimulating hormone ratio decrease was -0.8 (95% CI: -1.14 to -0.46) in the acupuncture combined with clomiphene group and -0.22 (95% CI: -0.47 to 0.01) in the clomiphene group. The adjusted between-group difference was 0.53 (95% CI: 0.24 to 0.82, p < 0.001). The levels of Agathobacter faecis increased, and those of Erysipelatoclostridium spiroforme, Streptococcus lutetiensis, and Lactococcus lactis decreased after acupuncture combined with clomiphene treatment (p < 0.05).Conclusion: Acupuncture combined with clomiphene may be safe and effective, reduce the luteinizing hormone-to follicle-stimulating hormone ratio, and improve insulin resistance in obese polycystic ovary syndrome, and these outcomes may be related to the gut microbiota.